ANALYSIS OF CAVITATION LEVEL IN WADASLINTANG HYDROPOWER PLANT USING THOMA CAVITATION FACTOR - Prasetyo, Budi; Saputra, Trisma Jaya; Fajarningrum, Nurmala Dyah (ROTOR, 2024)
Turbine damage can be caused by several causes, including damage to the turbine due to cavitation on the surface of its blades. Miscalculation of the position or location of the turbine can occur and will result in this cavitation. The Thoma cavitation factor is used to determine whether the turbine operation is safe from cavitation. This research was conducted at the Wadaslintang Hydroelectric Power Plant. The research used a quantitative descriptive research method. This study aims to determine the level of cavitation that occurs in the Francis turbine at an actual reservoir elevation of 169.23 meters above sea level with maximum guide vane openings to minimum guide vane openings. At variations in guide vane openings of 100% and 80% cavitation occurs, while at guide vane openings of 76%, 60%, 40%, and 20% cavitation does not occur. The larger the guide vane opening, the cavitation level is in a more dangerous condition because the difference between the cavitation factor and the critical cavitation factor is smaller, with the difference values ​​of 1.285073, 1.023435, 0.970782, 0.763080, 0.506127, and 0.253081, respectively. The smaller the guide vane opening, the smaller the risk of cavitation, but the power generated is also smaller. Safe operating conditions from cavitation with the greatest power are found at a guide vane opening of 76%-80%. Keywords: francis turbine, guide vane, cavitation, thoma cavitation factor.